Early development of sigma-receptor ligands. (January 2011) - Narayanan, Sanju; Bhat, Rohit; Mesangeau, Christophe; Poupaert, Jacques H; McCurdy, Christopher R
Sigma receptors (σ-1 and σ-2) are non-opioid proteins implicated in the pathophysiology of various neurological disorders and cancer. The σ-1 subtype is a chaperon protein widely distributed in the CNS and peripheral tissues. These receptors are involved in the modulation of K + - and Ca 2+ -dependent signaling cascades at the endoplasmic reticulum and modulation of neurotransmitter release. σ-1 receptors are emerging targets for the treatment of neurophychiatric diseases (schizophrenia and depression) and cocaine addiction. σ-2 receptors are lipid raft proteins. They are highly expressed on many tumor cells and hence considered potential targets for anticancer drugs. σ receptors bind to a diverse class of pharmacological compounds like cocaine, methamphetamine, benzomorphans like (±)-pentazocine, (±)-SKF-10, 047 and endogenous neurosteroids and sphingolipids. In this review we focus on the early development of σ receptor-specific ligands and radiolabeling agents.